An Election Monitoring Model in Indonesia Based on the Maqâsid Al-Syarî'ah Perspective: An Analysis of the Jâsir 'Audah Theory - Saputra, M. Reza (Yayasan Cahaya Generasi Positif, 2025)
This research analyses the election supervision model in Indonesia based on the perspective of maqâsid al-syarî'ah Jâsir 'Audah, focusing on protecting the five fundamental values in the electoral system. Implementing the 2024 General Election presents complex structural challenges, especially protecting KPPS officers with 181 recorded deaths. Using descriptive qualitative methods with a juridical-normative approach, this research examines Law no. 7 of 2017 concerning General Elections and integrates it with the theory of the Jâsir 'Audah system. The research results identified three main challenges: weak mechanisms for continuous health monitoring, unclear responsibilities of relevant agencies, and minimal community participation in monitoring the welfare of officers. The integration of maqâsid al-syarî'ah principles offers a holistic framework to strengthen the supervision system through the protection of hifdz al-nafs (soul), hifdz al-'aql (reason), hifdz al-nasl (offspring), and hifdz al-mâl (treasure). Policy recommendations include strengthening specific regulations, developing IoT-based technology for monitoring working conditions, and establishing rapid response protocols for vulnerable groups. This research concludes that the maqâsid system approach can answer the complexity of modern election challenges and strengthen the accountability of the Indonesian electoral system.